Taming social media: The effectiveness of behavior contract and self-management counseling for adolescents - Lianasari, Dewi; Fauzan; Astiwi Kurniati (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2025)
Social media addiction deeply affects students academically and psychologically. Most studies, especially in the Indonesian context, focused on social media addiction; some studies focused on the healing process, especially in the educational context. This study focused on the impacts of social media addiction counseling intervention on SMA Negeri 5 Magelang students. The researcher used a quasi-experimental design while adopting 2 of the four experimental groups configured using different techniques, each consisting of 7 students. The first of these groups used a behavior contract approach and the second used a self-management approach. The researcher adopted the Social Media Addiction Scale. The described data was analyzed and interpreted using paired and independent sample t-tests alongside effect size determination. The findings indicated that the counseling objectives were achieved by both groups, albeit with contrasting outcomes, particularly with the contract group averaging 20.29, and self-management group 9.29, statistically significant. The contract group achieved the most positive change of 2.535, however both groups showed statistically significant and differential positive results due to the techniques applied.The contract technique was statistically proven to be more effective than self-management. The role of behavior contract–integrated group counseling activities to build students' discipline, self-control, and responsible behavior on and off social media is invaluable. Counsellors are encouraged to use behavior contracts as a proactive approach to addressing social media overuse. Future research should prioritize larger sample sizes, consider potential moderating variables, and examine the long-term effects of such interventions through a longitudinal approach